"A nossa lâmpada não se apaga": The Mnemonic Return of Angola's Jonas Savimbi. (23rd March 2021) - Martins, Vasco
Abstract: Rehabilitating the legacy of deceased leaders is a phenomenon particularly salient in Southern Africa, insofar as memories of liberation wars provoke considerable debate. After a protracted civil war, Angolans remain divided about the contributions of their historical leaders. Jonas Savimbi sits at the center of this division, a binary representation of both heroism and villainy. Martins demonstrates how Savimbi's memory is invoked both as a moral source of hope for an alternative Angola—one imagined and disseminated by Savimbi and UNITA and appropriated by social protest—and as a technology of fear and control employed by the MPLA to assert political dominance.